2014
DOI: 10.1101/cshperspect.a018523
|View full text |Cite
|
Sign up to set email alerts
|

Novel Vaccination Strategies against Tuberculosis

Abstract: The tuberculosis (TB) pandemic continues to rampage despite widespread use of the BCG (Bacillus Calmette -Guérin) vaccine. Novel vaccination strategies are urgently needed to arrest global transmission and prevent the uncontrolled development of multidrug-resistant forms of Mycobacterium tuberculosis. Over the last two decades, considerable progress has been made in the field of vaccine development with numerous innovative preclinical candidates and more than a dozen vaccines in clinical trials. These vaccines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
108
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(110 citation statements)
references
References 162 publications
1
108
0
1
Order By: Relevance
“…10 The maintenance of specific immunity necessarily needs BCG bacilli to produce immunogenic substances, associated mainly with cell wall compounds. 12 Our last study confirmed that live mycobacterial L-forms persist in the blood of BCG vaccinated people. Forty five of 97 genetically tested blood cultures were identified as L-forms of mycobacteria belonging to Mycobacterium tuberculosis complex.…”
Section: Introductionsupporting
confidence: 68%
“…10 The maintenance of specific immunity necessarily needs BCG bacilli to produce immunogenic substances, associated mainly with cell wall compounds. 12 Our last study confirmed that live mycobacterial L-forms persist in the blood of BCG vaccinated people. Forty five of 97 genetically tested blood cultures were identified as L-forms of mycobacteria belonging to Mycobacterium tuberculosis complex.…”
Section: Introductionsupporting
confidence: 68%
“…Moreover, knowledge of absolute protein concentrations might help to prioritize immune-dominant target antigens of the human T cell response for subunit vaccines against tuberculosis. To prevent disease outbreak in individuals with latent tuberculosis, emphasis is now given to so-called multi-stage vaccines that express both antigens of dormant and replicating bacilli (Andersen and Kaufmann, 2014). The here-described method and resulting resource of Mtb protein concentrations during dormancy and resuscitation will facilitate identification of appropriate antigens for rational design of future multi-stage vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Strategies at Level 1.0 take advantage of a prime vaccination with conventional BCG to strengthen the immune response by booster with a subunit vaccine ( [50][51][52]. These are composed either of a dominant protein antigen formulated in an adjuvant, which stimulates T cells efficiently, or is expressed by a recombinant viral carrier [53]. None of these vaccine candidates induces protection at a level better than BCG in preclinical models, but all increase the protective efficacy caused by a BCG prime.…”
Section: Vaccination Strategiesmentioning
confidence: 99%